Hypoxia promotes noncanonical autophagy in nucleus pulposus cells independent of MTOR and HIF1A signaling. Issue 9 (1st September 2016) - Choi, Hyowon; Merceron, Christophe; Mangiavini, Laura; Seifert, Erin L.; Schipani, Ernestina; Shapiro, Irving M.; Risbud, Makarand V.
ABSTRACT: Nucleus pulposus (NP) cells reside in the avascular and hypoxic microenvironment of intervertebral discs. Importantly, many activities related to survival and function of NP cells are controlled by the HIF-family of transcription factors. We hypothesize that NP cells adapt to their hypoxic niche through modulation of macroautophagy/autophagy. In various cell types, hypoxia induces autophagy in a HIF1A-dependent fashion; however, little is known about hypoxic regulation of autophagy in NP cells. Hypoxia increases the number of autophagosomes as seen by TEM analysis and LC3-positive puncta in NP cells. Hypoxic induction of autophagy was also demonstrated by a significantly higher number of autophagosomes and smaller change in autolysosomes in NP cells expressing tandem-mCherry-EGFP-LC3B. Increased LC3-II levels were not accompanied by a concomitant increase in BECN1 or the ATG12–ATG5 complex. In addition, ULK1 phosphorylation at Ser757 and Ser777 responsive to MTOR and AMPK, respectively, was not affected in hypoxia. Interestingly, when MTOR activity was inhibited by rapamycin or Torin1, LC3-II levels did not change, suggesting a novel MTOR-independent regulation. Noteworthy, while silencing of HIF1A affected hypoxic induction of BNIP3, it did not affect LC3-II levels, indicating hypoxia-induced autophagy is HIF1-independent. Importantly, there was no change in the number of LC3-positive autophagosomes in NP-specific Hif1a null mice. Finally, inhibition of autophagic flux did not affect the glycolytic metabolism of NP cells, suggesting a possible nonmetabolic role of autophagy. Taken together, our study for the first time shows that NP cells regulate autophagy in a noncanonical fashion independent of MTOR and HIF1A signaling.